Structural insights into human SNF2/SWI2 chromatin remodeler SMARCAD1 and its role in DNA repair - Biasutto, A (2016)
ATP-dependent chromatin remodelers have been proposed to act sequentially, and to a certain extent non-redundantly, in the priming stages of the DNA Damage Response pathways by establishing chromatin in lesion sites ready to act as a scaffold for repair factors or to be displaced in order to allow DNA repair. Among remodeling factors proposed to play a role in DNA repair is SMARCAD1, a poorly characterized, non-canonical member of the SWR1-like family of SNF2/SWI2 superfamily of ATPases, which has recently been identified as a potential target for ATM/ATR phosphorylation at canonical and non-canonical sites upon DNA damage. The actual mechanism for SMARCAD1 recruitment and involvement in DNA remodeling is still unknown, and unlike most other chromatin remodelers, SMARCAD1 does not contain DNA- or histone-binding domains frequently accompanying such proteins. Instead, in addition to the core ATPase domain, only two CUE domains (a type of helical ubiquitin-binding domain) have been identified. This thesis presents the findings of an investigation intended to structurally characterize SMARCAD1 by dissecting and identifying its domain architecture, and examining the activity and ligand selectivity of its binding domains in the functional context of DNA damage repair. The solution NMR structure of the CUE1 domain is presented, describing a triple helix bundle consistent with other members of the family. Furthermore, a novel SUMO interacting motif was identified and through a combination of NMR titrations and phospho-proteomics analysis, shown to be constitutively phosphorylated which excludes the possibility of DNA damage dependent ATM targeting as the recruitment mechanism for DNA repair. Additionally, it is demonstrated that both CUE domains are poor binders of mono-ubiquitin, however CUE1 specifically mediates the high affinity binary interaction with the transcriptionally repressive master regulator KAP1. This interaction was shown to be independent of post-translational ubiquitylation but rather sustained through direct interaction with the dimeric RBCC domain of KAP1. Finally, mass spectrometry profiling of domain-dependent interactions (based on differential abundance relative to changes due to chemically induced DNA damage) suggests SMARCAD1 may be involved in p53 transcriptional regulation through interactions maintained with CUE1 prior to DNA damage, whereas the SIM domain selectively targets protein interactions upon DNA damage that simultaneously activate p53 transcriptional control and recruit SMARCAD1 to DNA damage repair pathways.